DETERMINANTS OF TAXPAYER COMPLIANCE IN PAYING MOTOR VEHICLE TAXES IN JEMBER - Yulianto -; Muhaimin Dimyati; Nanda Widaninggar (STIE Mandala Jember, 2022)
The purpose of this study is to examine and analyze the factors that influence taxpayercompliance in paying motor vehicle tax in Jember. The number of samples used in this studywere 100 respondents with the determination of the sample using accidental sampling method.Data collection using a questionnaire. The data analysis method uses data quality test analysis(validity test, reliability test), classical assumption test (normality test, multicollinearity test,heteroscedasticity test), determination coefficient, multiple regression analysis, t test and f test.The results of this study indicate that only the tax sanction variable has a partial effect, whiletaxpayer awareness, moral obligation, service quality, and tax sanctions have no significanteffect on taxpayer compliance. However, simultaneously it shows that the awareness oftaxpayers, moral obligations, quality of service, tax sanctions, and accountability of publicservices together have an effect on taxpayer compliance .Keywords: taxpayer awareness, moral obligation, service quality, tax sanctions, publicservice accountability, taxpayer compliance